2003
DOI: 10.1038/sj.bjp.0705279
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinins and tachykinin receptors in human uterus

Abstract: 1 Studies were undertaken to determine the nature of the receptors mediating contractile effects of tachykinins in the uteri of nonpregnant women, and to analyse the expression of preprotachykinins (PPT), tachykinin receptors and the cell-surface peptidase, neprilysin (NEP), in the myometrium from pregnant and nonpregnant women. 2 The neurokinin B (NKB) precursor PPT-B was expressed in higher levels in the myometrium from nonpregnant than from pregnant women. Faint expression of PPT-A mRNA was detectable in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 67 publications
9
56
0
Order By: Relevance
“…6). In recent studies, ␤-and ␥-PPTA were shown to be localized in Leydig cells of the human and mouse testis (47), and the expression of all PPTA, PPTB, and NK1 to -3 genes was also observed in nonneuronal cells of the mammalian uterus (48,49). Indeed, an elevation of some sexual steroid hormone-like substances was observed upon administration of Ci-TK-I on the ascidian gonad.…”
Section: Comparison Of Ci-tk-i and II With Several Vertebrate Tksmentioning
confidence: 98%
“…6). In recent studies, ␤-and ␥-PPTA were shown to be localized in Leydig cells of the human and mouse testis (47), and the expression of all PPTA, PPTB, and NK1 to -3 genes was also observed in nonneuronal cells of the mammalian uterus (48,49). Indeed, an elevation of some sexual steroid hormone-like substances was observed upon administration of Ci-TK-I on the ascidian gonad.…”
Section: Comparison Of Ci-tk-i and II With Several Vertebrate Tksmentioning
confidence: 98%
“…Reverse-transcription polymerase chain reaction (RT-PCR) assays were performed as previously described elsewhere (21,29). Total RNA from approximately 30 mg of human tissue was isolated using TriReagent (Sigma), and complementary DNA (cDNA) was synthesized using the Quantitect Reverse Transcription kit (Qiagen).…”
Section: Rt-pcr Experimentsmentioning
confidence: 99%
“…The genes encoding NKB (TAC3/Tac2), NK 3 R (TACR3/Tacr3), and the tachykinin-metabolizing enzyme neprilysin are expressed in human, mouse, and rat uteruses, and their expression and function vary with age, during the ovarian cycle, and during the course of pregnancy (20,22,(26)(27)(28)(29)(30). In the mammalian uterus, Tacr3 expression is strongly downregulated under conditions of estrogen dominance (17,24,(27)(28)(29)(30)(31). This is, to our knowledge, the only mechanism described so far of regulation of the tachykinin NK 3 receptor.…”
mentioning
confidence: 99%
“…No studies dealing with the distribution of this receptor in the uterus exist. However, it is known that SP influences the contractility of the oviduct (Patak et al 2003). NK1 receptor is responsible for the increase of vascular permeability in the uterine horn and cervix after the antydromic stimulation of the dorsal radices of lumbar nerves associated with the SP release form C-type nerve fibers (Pinter and Szolcsanyi 1995).…”
Section: Discussionmentioning
confidence: 99%